LITERATURE REVIEW: PENGARUH SUHU AIR ECONOMIZER DAN FLOW STEAM TERHADAP EFISIENSI BOILER CFB - faizal; Nanang Ruhyat (J-ENSITEC, 2025)
This study aims to analyze the effect of economizer water temperature and steam flow on boiler operational efficiency in Circulating Fluidized Bed (CFB) type Steam Power Plant (PLTU). The study was conducted through a literature review of a number of recent studies that examined the relationship between these two parameters and the thermal efficiency of the boiler system. The analysis shows that increasing the economizer water temperature from 65°C to 67°C can increase the efficiency up to 4%, while installing economizer in general can increase the efficiency up to 10%. On the other hand, excessive steam flow variation can cause temperature fluctuations and decrease efficiency, while optimal steam flow regulation is proven to increase heat recovery from flue gas and decrease operating costs. The optimal interaction between economizer water temperature and steam flow is proven to save fuel, reduce greenhouse gas emissions, and extend the service life of boiler components. This study concludes that the implementation of automatic control and real-time monitoring of both parameters is essential to improve energy efficiency, reduce maintenance costs, and support the sustainability of power generation systems.